Mechanical properties of copper/bronze laminates: Role of interfaces. (1st September 2016) - Ma, Xiaolong; Huang, Chongxiang; Moering, Jordan; Ruppert, Mathis; Höppel, Heinz Werner; Göken, Mathias; Narayan, Jagdish; Zhu, Yuntian
Abstract: Interfaces play a crucial role in mechanical behaviors of both laminated and gradient structured materials. In this work, copper/bronze laminates with varying interface spacing were fabricated by accumulative roll bonding and subsequent annealing to systematically study the interface effect on mechanical properties. Heterogeneities exist in chemical composition, grain size, hardness and texture across the interfaces. Simultaneous improvement of strength and ductility with decreasing interface spacing is found in tensile tests. Extra geometrically necessary dislocations (GNDs) are found to accumulate in the vicinity of interfaces, which is due to mechanical incompatibility across the interfaces. Importantly, an interface-affected zone spanning a few micrometers was found, which is not affected by interface spacing. These observations suggest the existence of an optimum spacing, which may produce the highest hardening capacity and ductility without sacrificing strength. Graphical abstract: